Screening of avocado rootstock material for tolerance to Phytophthora cinnamomi - Robbertse, P.J. (Petrus Johannes), 1932- (University of Pretoria, 2013)
Dissertation (MSc (Horticultural Science))--University of Pretoria, 2006.